Wet Torrefaction of forest Residues – Combustion Kinetics. (August 2015) - Bach, Quang-Vu; Tran, Khanh-Quang
Abstract: Fresh branches of Norway spruce and birch were torrefied in hot compressed water at varied temperatures(175, 200, or 225°C) and for 30 minutes. The combustion of untreated and torrefied branchesin synthetic air (21% O2 and 79% N2 ) wasexperimentally studied by means ofa thermogravimetric analyzer, followed by a kinetic analysis adopting the distributed activation energy model. It appears that, wet torrefaction has significant effects on the combustion reactivity of forest residues. Compared with the raw materials, wet-torrefied branches are less reactive during devolatilization, but more reactive in the char combustion stage.